Genesis of environmental education policy in Botswana: construction and interpretation - Ketlhoilwe, Mphemelang Joseph (Rhodes University, Faculty of Education, Department of Education, 2007)
This study is based on the 1994 Revised National Policy on Education (Botswana Government, 1994) that introduced environmental education into the Botswana's education system. The main goals of this study were to understand the genealogy of and to critically analyze governmentality associated with environmental education policy in Botswana. Drawing on a post-structural genealogical approach to the subject matter (following Foucault) global historical events and their influence on policy in Botswana, views on environmental education and interpretation, and power relations in environmental education policy discourses were investigated. An investigation was conducted through document analysis, interviews, focus group discussions and observations. The analysis revealed that power relations have historically transcended environmental education policy discourses from global, regional to national levels. The exercise of power through international bodies, and bilateral and multilateral agreements has impacted on Botswana enabling her to enact policies to address socio-ecological crises or regulating them to sustainably utilize natural resources. However, evidence has shown that although Botswana accepted and introduced environmental education, structures were not ready for its implementation and hence some contextual problems are experienced by teachers in schools. The Revised National Policy on Education (RNPE) was constructed through a consultative process, but the final decision on what goes into the policy text was decided from the top (i.e. by the Ministry of Education senior officials). It emerged from this study that Botswana has inconsistently adopted sustainability and conservation-protection discourses in environmental education policy. The mix of the two discourses shows continuity of the protectionist-conservationist discourses and emergence of the current sustainable use discourse, creating a complex discourse environment. The study also revealed that in including these primarily western scientific discourses, other discourses were marginalized or excluded, which revealed continuity with colonial education discourses. The findings also revealed variance in the understanding of environmental education. The majority of the teachers understood and normalised new knowledge in environmental education as Environmental Science or Science, and equated environmental management activities with environmental education. Teachers deployed new governmentalities and normalizing strategies by following the traditional conservation and science epistemological and pedagogical discourses. They exercised various self-governing strategies to respond to the RNPE requirement regarding environmental education. The findings highlight the need for re-conceptualization of environmental education at macro(at Ministry of Education) and micro level. There is a need to harmonize the variation in policy interpretations and clarification of the conservation/environmental education and sustainability discourses running parallel in schools or to work more explicitly with multiple discourses. It has also emerged that teacher support mechanisms need review to enhance policy implementation. The study recommends that further and explicit analysis of environmental education discourses is critical for shaping the future of environmental education policy development and interpretation within Botswana's education system.
Keywords: Environmental education -- Botswana; Education and state -- Botswana